2007
DOI: 10.1303/aez.2007.643
|View full text |Cite
|
Sign up to set email alerts
|

Differential tissue distribution of two acetylcholinesterase transcripts in the German cockroach, Blattella germanica

Abstract: Recent studies have revealed that non-Cyclorrhapha insects possess two acetylcholinesterases (AChEs): Drosophila Ace-orthologous (o-Ace) and -paralogous (p-Ace) forms. In these insects, p-Ace is considered as a neural target of insecticides because mutations conferring insecticide insensitivity have been consistently identified in equivalent forms from various insects. To clarify the functional differentiation between the two AChE isoforms, we characterized the expression of two AChE genes in nerve cell-rich a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
3
3
1
Order By: Relevance
“…3). This finding is in contrast to a previous report in which BgAChE2 is more extensively distributed in the PNS based on quantitative profiling of BgAChE2 transcription (Mizuno et al. , 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…3). This finding is in contrast to a previous report in which BgAChE2 is more extensively distributed in the PNS based on quantitative profiling of BgAChE2 transcription (Mizuno et al. , 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…The transcript levels of TcAce1 at these stages and in the brain were 1.2- to 8.7- fold higher than those of TcAce2 ( P ≤0.05), indicating that TcAce1 transcript is more abundant than TcAce2 at all the developmental stages and in the brains. Our data are consistent with those found in other insect species, including B. germanica 18, the diamondback moth ( Plutella xylostella )28, the oriental tobacco budworm ( Helicoverpa assulta )29, and the mosquito ( Culex pipiens )30. Nevertheless, the relative transcript abundances of the two genes vary significantly among the insect species and different tissues of the same species, ranging from 13- to 250-fold in the different tissues of P. xylostella 28 and 3-fold in the nerve cord of B. germanica 18.…”
Section: Discussionsupporting
confidence: 93%
“…It is noteworthy that the knockdown of Bgace2 mRNA did not alter Bgace1 expression and vice versa, which might suggest noncoordinated transcription and thus, a functional differentiation of ace genes. Thus, RNAi appears as a valuable tool to discriminate the activities of both AChE1 and AChE2 in non-Cyclorrhapha insects, besides the inhibitor sensitivity studies previously reported (Bourguet et al, 1996;Huchard et al, 2006;Mizuno et al, 2007). In this sense, our data agree with previous data that indicate a minor, but measurable contribution (ca.…”
Section: Discussionsupporting
confidence: 92%
“…Altogether, the similar depletion of Bgace1 and Bgace2 mRNAs (95%) and the differential reduction in AChE activity by either dsBgace1 or dsBgace2, suggest that AChE1 is responsible for approximately 65e75% of total AChE activity. This confirms that AChE1 is mainly responsible for AChE activity in ganglia of B. germanica, as suggested by previous findings that showed predominant transcription of Bgace1 in nerve tissues Mizuno et al, 2007). A moderate, but significant contribution to ACh hydrolysis is accomplished by AChE2, which suggests either a low or localized enzymatic activity of the ace2 protein.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation